Slow speed resistance exercise training in children with polyarticular juvenile idiopathic arthritis - Sule SD (Dove Medical Press, 2019)
Sangeeta D Sule,1 Kevin R Fontaine21Division of Rheumatology, Children’s National Health System, Washington, DC 20010, USA; 2Department of Public Health, School of Public Health, University of Alabama at Birmingham, Birmingham, AB, USABackground: Juvenile idiopathic arthritis (JIA) is an inflammatory autoimmune disease that can cause severe impairment and disability. Exercise is recommended to preserve joint mobility and function. Our objectives were to assess the safety, feasibility, and effects of slow speed resistance exercise in children with polyarticular JIA.Methods: Patients were recruited from a pediatric rheumatology clinic at an urban hospital and randomized to exercise or control groups. In the intervention group, slow speed resistance exercise with individualized instruction by a certified trainer was performed 1–2 times per week for 12 weeks. The control group performed home-based aerobic exercise 3 days per week for 12 weeks. Pre and post-body composition measurements by dual-energy X-ray absorptiometry; aerobic fitness by peak oxygen uptake during cycle ergometry; isometric muscle strength; and quality of life measures were obtained.Results: In the exercise group, 9/17 (53%) completed any exercise training. Of these nine subjects, five (55%) completed all 12 weeks of the protocol. In the control group, 8/16 (50%) reported compliance with the recommended aerobic exercise training at least one time per week. Only 2 subjects (12%) reported exercising more than once per week. There was no significant difference between pre- and post-measurements in any category in the exercise group. There was also significantly elevated body fat in both groups with only 17% in the control group and 23% in the exercise group meeting recommended <30% total body fat levels.Conclusions: Children with JIA participated safely in this resistance exercise protocol. The exercise was well-tolerated with no serious adverse events noted. While individual subjects reported improvement in fatigue and improved energy, there was no statistical difference in pre- and post-exercise measures of body composition or quality of life. Identifying ways to improve adherence and encourage exercise in children with JIA is important.Keywords: exercise, juvenile arthritis, body composition